2021 Compounding Misfortunes : An Update to the Study - World Bank Group; UNHCR; World Food Programme; Joint Data Center on Forced Displacement (World Bank, Washington, DC, 2021)
COVID-19 (coronavirus) has had an enormous impact on nearly every country in the world. However, Iraq, Jordan and Lebanon were already facing difficult to extreme circumstances even before the pandemic erupted, making them particularly vulnerable. This report looks at the impact of the pandemic, associated lockdowns and economic shocks and other misfortunes which have compounded the crisis, such as sharply lower oil revenues in Iraq and the Port of Beirut explosion in Lebanon, as well as political instability in both. The report estimates that 4.4 million people in the host communities and 1.1 million refugees or IDPs were driven into poverty in the immediate aftermath of the crisis, and while this considers all of Lebanon, it only includes three governorates in Jordan and the Kurdistan Region of Iraq, due to data limitations. A response commensurate with the magnitude of the shock is needed to prevent further misery. The poverty impact of COVID-19 and the ensuing confinement policies and economic contractions have been felt throughout the world, not least by marginalized communities. However, COVID-19 has compounded existing vulnerabilities or crises in Jordan, the Kurdistan Region of Iraq (KRI) and Lebanon. Syrian refugees – most of whom have been displaced for up to nine years – are particularly exposed given their perilous pre-crisis situation. Host communities in these three countries, who have supported and accommodated such large numbers of refugees, have also been heavily affected; all three countries were in strained positions prior to COVID-19, ranging from economic stagnation and high public debt in Jordan, to a collapse in public revenues due to international oil price shocks in KRI, to complete political and economic crisis in Lebanon. By March 2020, all three countries had witnessed their first cases of COVID-19 and introduced stringent containment policies ranging from partial closures of schools and shops to full curfew. While these measures were initially largely successful in containing the spread of the pandemic, they also led to a decline in economic activity across most sectors, particularly in the informal market. In Jordan and Iraq, the losses are estimated at around 8.2 and 10.5 percent of 2019’s GDP respectively. In Lebanon where the COVID-19 crisis is compounded by economic and political crises the losses are much higher, around 25 percent of GDP. Lebanon has experienced inflation of over 100 percent, largely due to its import dependence and currency depreciation. Unsurprisingly, given the magnitude of these shocks, recent rapid needs assessments and UNHCR administrative data show that refugees, who are highly concentrated in low-skilled jobs in the informal sector, have had to reduce food intake, incur additional debt and in some instances suffered eviction.